Cyberpunk 2077 : big city dreams - Sztybor, Bartosz; Ostrowski, Krzysztof, 1976-; Titov, Roman; Bidikar, Aditya; Bergara, Matías, 1984- (Dark Horse Books, 2022)
"Two low-level criminal partners begin to drift apart as they struggle to survive in Night City"--